Pericardial tamponade masking associated pulmonary thrombo embolism in a case of adeno carcinoma of lung - Kandasamy, Srinivasan; Tadi, Monica E. Florence; Rudrapogu, John Satish; Biju, Govind; Boddikura, Chaitanya; Naralasetty, Anil Kumar (International Journal of Research in Medical Sciences, 2017)
This case report describes a patient admitted with shortness of breath of 15 days duration and found to have cardiac tamponade, which masked concomitant pulmonary embolism that was diagnosed by echocardiographic signs of dilate RA/RV with PAH only after successful pericardiocentesis. Subsequently patient was found to have widely metastatic adenocarcinoma of lungs. This case emphasizes the diagnostic challengewhen cardiac tamponade is associated with pulmonary thromboembolism and requires high index of clinical suspicion in patients with underlying malignancy.